2022
DOI: 10.1111/raq.12754
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of the giant river prawnMacrobrachium rosenbergii: A review for a growing industry

Abstract: The giant river prawn, Macrobrachium rosenbergii, is a major focus of aquaculture in tropical and sub-tropical regions around the globe. Over the last 30 years, culture of M. rosenbergii has increased exponentially as demand has risen both for domestic consumption and for international export trade. As with many aquaculture species increases in production have been accompanied by the emergence of diseases affecting yield, profit and trading potential. Disease-causing agents include pathogens infecting other cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 195 publications
0
10
0
Order By: Relevance
“…Disease outbreaks caused by viral and bacterial pathogens have resulted in significant declines in the production of farmed crustaceans [23]. M. rosenbergii, an economically important cultured crustacean species, has experienced mass mortalities as a consequence of infections with various pathogens, including Taura Syndrome Virus (TSV), DIV1, Vibrio alginolyticus, Vibrio cholerae, A. caviae, and A. veronii [2]. In this study, strain JDM1-1 was identified as A. veronii based on the analysis of molecular information, including 16S rRNA and gyrB sequences, as well as biochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease outbreaks caused by viral and bacterial pathogens have resulted in significant declines in the production of farmed crustaceans [23]. M. rosenbergii, an economically important cultured crustacean species, has experienced mass mortalities as a consequence of infections with various pathogens, including Taura Syndrome Virus (TSV), DIV1, Vibrio alginolyticus, Vibrio cholerae, A. caviae, and A. veronii [2]. In this study, strain JDM1-1 was identified as A. veronii based on the analysis of molecular information, including 16S rRNA and gyrB sequences, as well as biochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…China has become the world's largest producer of Macrobrachium rosenbergii, a giant freshwater prawn, with an increase from 136,415 tons in 2000 to 177,836 tons in 2022 according to the China Fishery Statistical Yearbook [1]. M. rosenbergii is one of the most economically cultured freshwater species and is primarily found in tropical and sub-tropical areas [2]. With the rapid expansion of M. rosenbergii aquaculture in China, there has been a concurrent increase in the occurrence of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…: 919-927) [52]. [6]. Tis necessitates the strictest doable biosecurity measures being put in place, along with ongoing vigilance for both new and existing pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have recently been a number of concerns regarding the sustainability of E. sinensis aquaculture. Similar to shrimp or prawn farm operations, when new aquaculture techniques appear at the same time as a concentrated push to boost crab farming production, the danger of crab disease also increases [6]. Numerous diseases, induced by bacterial, viral, fungal, and other eukaryotic pathogens, have been found in cultivated E. sinensis.…”
Section: Introductionmentioning
confidence: 99%
“…Central to this success is the giant freshwater prawn, also known as Macrobrachium rosenbergii, an important species in aquatic farming. Originating from the diverse ecosystems of the Indo-Pacific, this prawn has transcended its native habitat to become a linchpin in aquaculture endeavors spanning tropical and subtropical regions (Hooper et al, 2023). South and Southeast Asia stand as compelling stages for this narrative, with Thailand and Taiwan rising as virtuoso performers in the art of prawn cultivation.…”
Section: Introductionmentioning
confidence: 99%